Cinesofia a sétima arte em devaneio - Vaccari, Ulisses Razzante (Editora Oficina Universitária, 2022)
"The need to think about cinema from a philosophical point of view is linked to the urgency of reconquering the most fundamental meaning of film in contemporary life. More than a century after the invention of cinema, it is possible to say, without further ado, that film, in general, has lately fallen into a kind of crisis. It is as if, more than a hundred years after the first cinematic experiences, the question about the essence of cinema has become more urgent than ever."